COMMEMORATIVE PRACTICES IN KABARDINO-BALKARIA ASSOCIATED WITH THE GREAT PATRIOTIC WAR - Tetuev, Alim Inzrelovic (History, Archeology and Ethnography of the Caucasus, 2021)
he study reviews commemorative practices regarding the Great Patriotic War in Kabardino-Balkaria. The state of historiography and the sources of the question under study are analyzed; its relevance, novelty, theoretical and practical significance are discussed. The article considers the regulatory legal acts of the Russian Federation and Kabardino-Balkaria, which provide for various commemorative practices to preserve the memory of the Great Patriotic War. The experience of state, municipal authorities and civil society institutions in the formation of commemorative practices at the federal, regional, municipal and family levels is summarized. It is noted that the main national symbols of memory of the Great Patriotic War are the Victory Day, the Day of Remembrance and Mourning, the Day of the Unknown Soldier and other dates specified in the Federal Law “On Days of Military Glory and Memorable Dates of Russia”. Places of memory in Kabardino-Balkaria are revealed and studied: military cemeteries, mass graves, memorial places of military operations of soldiers of the Red Army, memorial plaques, memory books, museums of military glory, as well as streets, squares, schools named after the heroes of the Great Patriotic War. The experience of the work of state, municipal authorities and civil society institutions in the search and establishment of the names of the victims, the burial of their remains, the improvement of monuments, the reconstruction of the events of the war years that took place in the Elbrus region in 1942–1943 is generalized. Commemorations created at the initiative of family members, their relatives and veterans are analyzed. The activity of social movements, actions such as “Eternal regiment”, “Candle of memory” to preserve personal memory of the generation of the Great Patriotic War in the family is covered. An analysis of the problem under study demonstrates that commemorative practices create conditions for preserving the memory of the Great Patriotic War and consolidating society.